2020
DOI: 10.1111/nyas.14374
|View full text |Cite
|
Sign up to set email alerts
|

Detection and analysis of enamel cracks by ICG‐NIR fluorescence dental imaging

Abstract: Cracked teeth are the third most common cause of tooth loss, but there is no reliable imaging tool for the diagnosis of cracks. Here, we demonstrate the feasibility of indocyanine green near‐infrared fluorescence (ICG‐NIRF) dental imaging for the detection of enamel cracks and enamel–dentin cracks in vitro in the first (ICG‐NIRF‐I, 700–950 nm) and second (ICG‐NIRF‐II, 950–1700 nm) imaging windows with transmission excitation light, and compared ICG‐NIRF with conventional NIR illumination‐II (NIRi‐II) and X‐ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…In addition, our previous study in human dentistry also demonstrated that some dental tissues, e.g., enamel, became transparent in NIR-II region, which could obtain a higher efficiency in the detection of dental diseases. 28 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our previous study in human dentistry also demonstrated that some dental tissues, e.g., enamel, became transparent in NIR-II region, which could obtain a higher efficiency in the detection of dental diseases. 28 …”
Section: Discussionmentioning
confidence: 99%
“… 11 , 19 27 Our previous studies have successfully demonstrated ICG-NIR fluorescence (ICG-NIRF) dental imaging in both human-extracted tooth and rat models. 17 , 28 32 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Li et al [ 71 ] confirmed the practicability of using indocyanine green-assisted near-infrared fluorescence (ICG-NIRF) imaging to detect enamel-dentin and enamel cracks in vitro . ICG-NIRF imaging can detect more cracks than using only the second region of near-infrared light, which detects the cracks and their depths not detected by CT and X-ray.…”
Section: Diagnosismentioning
confidence: 99%
“…Better resolution over the result was obtained compared with QCT, QUS, and DEXA. These traditional techniques had the drawback of inaccurate values and exposure to radiation ( 51 , 55 ). In another work, the surface roughness of rot carriers was analysed using optical profilometry.…”
Section: Type Of Optical Mems Sensors With Applicationmentioning
confidence: 99%